A Bioinformatical Approach to Study the Endosomal Sorting Complex Required for Transport (ESCRT) Machinery in Protozoan Parasites: The Entamoeba histolytica Case - López-Reyes, Israel; Bañuelos, Cecilia; Betanzos, Abigail; Orozco, Esther (IntechOpen, 2011)
None